Administration of Ashitaba (Angelica Keiskei) leaves extracts prevented Superoxide Dismutase (SOD) Reduction and Malondialdehyde (MDA) elevation in overtrained-male wistar rats (Rattus norvegicus) - Ronald Suryaprawira; Alex Pangkahila; Wimpie Pangkahila (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: The aging process is caused by several factors, one of which is the accumulation of oxidative damage caused by high free radicals in the body. Ashitaba (Angelica keiskei) leaves extract contains flavonoids, polyphenols, tannins, and antioxidant capacity. This study aimed to prove that administration of Ashitaba leaves extracts prevent superoxide dismutase (SOD) reduction and malondialdehyde (MDA) elevation in overtraining male Wistar rats (Rattus norvegicus). Methods: This study was an experimental study with randomized pretest-posttest control group design. The subjects used in this study were 16 male Wistar rats, healthy, aged 6 months, and weighing 180- 200 grams. The control group was given overtraining two hours after aquabidest 2 cc treatment (P0), and the treatment group was given overtraining two hours after administration of Ashitaba leaves extract of 20 mg/kg BW/day (P1). Before and after treatment for 14 days, blood sample were drawn through canthus medial orbital sinus to measure the level of SOD and MDA using the ELISA method. Results: The results showed in control group there was a decrease in SOD levels (from 8.58±0.78 ng/mL to 5.93±1.27 ng/mL; p<0.001) and increased MDA levels (from 2.75±0.19 nmol/mL to 3.28±0.23 nmol/mL; p= 0.001). In treatment group there was no change in SOD levels (from 8.90±0.61 ng/mL to 8.57±0.49 ng/mL; p= 0.217) and there was no change in MDA levels (from 2.67±0.33 nmol/mL to 2.62±0.24 nmol/mL; p= 0.693). Conclusion: It can be concluded that administration of Ashitaba leaves extracts prevented SOD reduction and MDA elevation in overtraining male Wistar rats.